A monetary and fiscal history of Latin America, 1960-2017 - Kehoe, Timothy Jerome 1953-; Nicolini, Juan Pablo (University of Minnesota Press, 2021)
"A major, new, and comprehensive look at six decades of macroeconomic policies across Latin America."
Keywords: 1960-2017; Finanzgeschichte / (DE-627)091359872 / (DE-2867)11533-3; Geldgeschichte / (DE-627)091362210 / (DE-2867)11416-0; Entwicklung / (DE-627)091357322 / (DE-2867)10513-0; Lateinamerika / (DE-627)091374464 / (DE-2867)17990-1; Latin America / Economic conditions / 20th century; Latin America / Economic conditions / 21st century; Aufsatzsammlung; Fallstudiensammlung